POSTGRADUATE EDUCATION FUNCTIONING PATTERNS OF TOURISM SPHERE SPECIALISTS IN SWITZERLAND - Наталія Закордонець (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
Functioning patterns of postgraduate education of tourism sphere specialists in Switzerland have been established. The competences of tourism sphere specialist, the formation of which programs of postgraduate education are focused on have been considered. The benefits of educational qualification of Masters in Business Administration with a major specialization in tourism have been outlined. The characteristics of the core curriculum of the Doctor of Management of leading universities in the field of tourism education have been determined. The performance criteria of postgraduate education system functioning of tourism sphere specialists in Switzerland have been revealed.